Una nota sobre algunas estrategias representativas en muestreo y su validez práctica (2011)
A sampling strategy is the combination of a sampling design and an estimator. In this paper is presented the problem of choosing a representative strategy with respect to some auxiliary variables, in order to increase the precision of the resulting estimates for the population total. There exist several sampling designs and estimators that induce a representative strategy, but it is concluded, by means of some empirical simulations, that it is not always better the choice of an strategy given by the use of a calibration estimator under a balanced sampling design, as one may suppose.